Vegetation carbon sequestration in Chinese forests from 2010 to 2050. (14th October 2016) - He, Nianpeng; Wen, Ding; Zhu, Jianxing; Tang, Xuli; Xu, Li; Zhang, Li; Hu, Huifeng; Huang, Mei; Yu, Guirui
Abstract: Forests store a large part of the terrestrial vegetation carbon (C) and have high C sequestration potential. Here, we developed a new forest C sequestration (FCS) model based on the secondary succession theory, to estimate vegetation C sequestration capacity in China's forest vegetation. The model used the field measurement data of 3161 forest plots and three future climate scenarios. The results showed that logistic equations provided a good fit for vegetation biomass with forest age in natural and planted forests. The FCS model has been verified with forest biomass data, and model uncertainty is discussed. The increment of vegetation C storage in China's forest vegetation from 2010 to 2050 was estimated as 13.92 Pg C, while the average vegetation C sequestration rate was 0.34 Pg C yr −1 with a 95% confidence interval of 0.28–0.42 Pg C yr −1, which differed significantly between forest types. The largest contributor to the increment was deciduous broadleaf forest (37.8%), while the smallest was deciduous needleleaf forest (2.7%). The vegetation C sequestration rate might reach its maximum around 2020, although vegetation C storage increases continually. It is estimated that vegetation C sequestration might offset 6–8% of China's future emissions. Furthermore, there was a significant negative relationship between vegetation C sequestration rate and C emission rate in different provinces of China, suggesting that developed provinces might need to compensate for undeveloped provinces through C trade. Our findings will provide valuable guidelines to policymakers for designing afforestation strategies and forest C trade in China.